Three irises - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows three irises with foliage. Two of the flowers and the foliage have been extensively hand colored. The top flower is yellow and the bottom flower is red. The middle flower has been touched up with a light shower of red but is primarily gray in the photograph.